Evaluation of sustainable development of dairy industry in Poland - Wiater, Józefa; Boruszko, Dariusz; Dąbrowski, Wojciech; Żyłka, Radosław; Antonowicz, Sylwia (Economics and Environment, 2019)
Dairy plants development should be based on the principle of sustainable development, which is present both in National Environmental Policy and European Union environmental protection policy. It is in compliance with Best Available Technology (BAT). Technology connected with recovering energy from sewage, sewage sludge and production waste is gaining more and more interest. The authors of this article have been cooperating with several production plants in podlaskie province for many years through conducting scientific research and preparing environmental reports or integrated permissions (IPPC). The article discusses the most crucial aspects of sustainable development of the dairy industry. Also, the results of environmental aspects (water consumption, sewage production and treatment, wastes, gas and noise emissions, energy consumption) connected with dairy plants management are presented.